Pedagogical strategies used for the teaching of human movement sciences and student perception about its impact on learning (Revista Electrónica Calidad en la Educación Superior, 2018)
The purpose of this research was to analyze the pedagogical strategies used for the teaching of human movement sciences and their impact on the learning of higher education students. A qualitative study was designed, with focus group, participant observation and teacher evaluation questionnaire. Participants were 32 students from 2 public and 2 private universities; 12 teachers from the four universities also participated. The conclusion is that most of the teachers were perceived by the students as clearly transmitters of information with class environments superficial and not significant. On the other hand, it was shown that those teachers, who showed interest, respect and concern for their students, the class was considered significant to learn.